Civil liability in pharmacy - O. H. Aleksieiev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
The aim to characterize civil liability as a component of legal liability in pharmacy.